ANALISIS TEKNO-EKONOMI PEMAKAIAN SUMUR HORIZONTAL SEBAGAI SOLUSI DARI PENGEMBANGAN RESERVOIR TIPIS DAN BERKUALITAS BURUK - Novico Kasameika, Andhyka
Hydrocarbon production in Indonesia is decreasing while the hydrocabon consumption is increasing each year. When the oil price is still high, a lot of fields that has been explored is abandoned due to the small size and bad quality reservoir. But as the time goes by, those reservoirs are now wanted because of the decreasing amount of reserves. In this study, simulation is run for low permeability and multiple thin layer reservoir which is produced for 20 years long. This study is doing the analysist on the tech and economic evaluation on how that reservoir is developed using horizontal well. Simulation is run using the software CMG. This software is used to see the reservoir performance and to see oil and gas production while the simulation is running. There are 3 cases that will be examined during this study. All of cases is run using 4 production wells and 1 injection wells. The water injection is started since the beginning of simulation. First case is defined by producing only in 1 productive layer for 20 years. For the second case, all productive layer is produced commingle for 20 years. And the last, simulation is run on a scheduled basis. Production is done on a certain layer until that layer is not so productive, and will be continued on the next layer within 20 years. As a result, there are significant oil production differences of 3 cases. On the first case, the simulation obtained 204.6 thousands of barrel oil, then the second case resulted 443.7 thousands of barrel oil and the last case produced 553.2 thousands of barrel oil. But after economic evaluation is run, the fields is not so profitable due to the cost that contractor needs to pay is uncomparable to the contractor’s income. The best case for the contractor’s net present value after 10 percents of discount rate is Case 2 which results150,000 USD. This study is learning about the methods of reservoir production management, and knowing the most effective way to produced a multi thin layer and low permeability reservoir.